Islam dan Demokrasi di Malaysia: Hubungan Agama dan Negara yang Unik - Ahmad Sahidah (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2011)
Some Malaysian people has repudiated their country as an Islamic state. At the same time, the other people, especially Muslims, asserted that Malaysia already is and ought to be regarded such. The participation of Malaysia in Organization of the Islamic Conference and the enactment of syari’ah in its law system has evident in it self. From the discourse of Islamic politics, however, the Islamic state is not a monolithic concept. Interestingly, after the Pakatan Rakyat won many seats in parliament in 2008, politicians has paid attention on welfare state issues, not Islamic state, as a common denominator between Islamic party and secular party that has made a shared coalition to be an alternative from the National Front.